Sudden Infant Death Syndrome - Atılmış, Ümit Ünüvar; Dokgöz, Halis; Yemişçigil, Ali (The Bulletin of Legal Medicine, 2006)
Sudden infant death syndrome (SIDS) is the sudden death of an infant under 1 year of age which remains unexplained after a thorough case investigation, including performance of a complete autopsy, examination of the death scene, and review of the clinical history. It is a major cause of postneonatal mortality in developed countries. Generally, the infant is found dead after having been put to sleep and displays no signs of having suffered. Despite many years of research, underlying pathophysiology and mechanism of SIDS still remained controversial but numerous risk factors have been defined. In this article; SIDS and possible risk factors are reviewed and the precautions to decrease the incidence of SIDS and important role of autopsy and history were emphasized. Key words: Sudden infant death syndrome, infant, risk factors, sleep, autopsy